ASSESSING UNPI’S STUDENTS CRITICAL THINKING SKILLS IN DISCOURSE ANALYSIS - Rizky Tazkiyatul Ummami; Yusup Supyani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
The research aims to show the students in Universitas Putra Indonesia (UNPI) represent impact of Critical Thinking their idea in Discourse Analysis and to identify the students in showing their scientific interpreting, analyzing and evaluating idea in Discourse Analysis. The purpose of this study is to investigate the students critical thinking skills in Discourse Analysis. In the processing of this research, the writer applies descriptive quantitative research using one group pretest-posttest design method by Mike Allen (2017). This research used theories of Formative Assessment by William & Black on International Journal (2012), Critical Thinking Skill by Facione (2015) and Discourse Analysis by Brian Paltridge (2012). The researcher conducts three stages of research (pre-assessment – treatment – post-assessment). The result of this research shows that the students represents an improvement of six aspects critical thinking (interpretation, analysis, inference, evaluation, explanation, self-regulatory) in Discourse Analysis.